Beaufort trout MicroPlex: a high‐throughput multiplex platform comprising 38 informative microsatellite loci for use in resident and anadromous (sea trout) brown trout Salmo trutta genetic studies. Issue 6 (4th June 2013) - Keenan, K.; Bradley, C. R.; Magee, J. J.; Hynes, R. A.; Kennedy, R. J.; Crozier, W. W.; Poole, R.; Cross, T. F.; McGinnity, P.; Prodöhl, P. A.
<x xml:space="preserve">Abstract</x> A flexible panel consisting of 38 informative microsatellite markers for Salmo trutta is described. These markers were selected from a pool of over 150 candidate loci that can be readily amplified in four multiplex PCR groups but other permutations are also possible. The basic properties of each markers were assessed in six population samples from both the Burrishoole catchment, in the west of Ireland, and Lough Neagh, in Northern Ireland. A method to assess the relative utility of individual markers for the detection of population genetic structuring is also described. Given its flexibility, technical reliability and high degree of informativeness, the use of this panel of markers is advocated as a standard for S. trutta genetic studies.